Alinhamento de expectativas e desempenho organizacional: um estudo sobre os métodos ágeis de gestão - Coelho, Mauricio Taves Cordeiro (2012)
The adoption of agile software development management methods has been a global trend, considering companies in the technology sector. Brazilian companies operating in this market are not detached from this tendency, since the goal of these methods is to address a common scenario to any of these organizations: dealing with the difficulty of adequately modeling the usually complex problems that are the goal of building a specific software and with the constant change of requirements that this situation represents, further enhanced by the frenetic dynamics of information dissemination in the XXI century, besides modifying a chronic perception of failure that pervades the sector, aiming to deliver quality products to its customers with maximum speed. Internal aspects such as increasing productivity and reducing rework are also part of the objectives of the adoption of these methodologies. This study aims to assess the human and cultural aspects involved and identify the convergence between the expectations of the company and employees when adopting agile management, based on field research that captured the reactions of a group of respondents to the implementation of these methods at Modulo Security Solutions, a Brazilian technology and services company, after two years of extensive internal use. The results indicate the success of the implementation, with positive reactions from employees, despite the need for addressing human aspects to adjust the model and that the negative impact of local and organizational cultures have been widely perceived.